2005
DOI: 10.1111/j.1740-8261.2005.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Diagnosis of Transposition of the Great Arteries in a Neonatal Foal

Abstract: The clinical and echocardiographic findings in a 19-h-old female foal with a ventricular septal defect, patent foramen ovale, patent ductus arteriosus, and complete transpositon of the great vessels are described. Clinical signs were suggestive of complex congenital heart disease and echocardiography of the foal allowed definitive diagnosis prior to postmortem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The presence of PFO or PDA in this study must be interpreted with caution. Physiologic or functional closure of the ductus arteriosus occurs in the equine neonate between 48 and 72 hours of age, 34 whereas complete anatomic closure could be delayed until 4 days of age 3,15 . Physiologic or functional closure of the foramen ovale occurs immediately postpartum; however, anatomic closure does not occur until 15 days to 9 weeks of age 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of PFO or PDA in this study must be interpreted with caution. Physiologic or functional closure of the ductus arteriosus occurs in the equine neonate between 48 and 72 hours of age, 34 whereas complete anatomic closure could be delayed until 4 days of age 3,15 . Physiologic or functional closure of the foramen ovale occurs immediately postpartum; however, anatomic closure does not occur until 15 days to 9 weeks of age 3 .…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is important to recognize the clinical findings associated with such defects early in the course of medical evaluation of neonatal foals, as the presence of a defect can alter the prognosis and course of treatment. The available reports in the peer‐reviewed literature include pathology reports 2–5 single case reports, and small case series describing congenital cardiac defects in ≤5 foals 1,6–33 . Authors of case reports have suggested an association between the Arabian breed and the occurrence of cardiac defects, but this suspicion has not been confirmed 1,22–34 .…”
mentioning
confidence: 99%
“…2000; Seco Diaz et al . 2005; Sleeper and Palmer 2005; Schmitz et al . 2008) with occasional case descriptions of acquired cardiac disease (Reef 1987; Collatos et al .…”
Section: Introductionmentioning
confidence: 99%
“…Standard transthoracic 2D, M-mode and Doppler techniques were adapted from the mature horse and measurements first reported for Thoroughbred and pony foals in 1984 (Lombard et al 1984;Stewart et al 1984). Since that time, published reports involving the echocardiographic evaluation of the foal have primarily focused on cases of congenital cardiac defects (Pipers et al 1985;Reef et al 1987;Sojka 1987;Wilson and Haffner 1987;Ecke et al 1991;Hinchcliff and Adams 1991;Chaffin et al 1992;Schober et al 2000;Seco Diaz et al 2005;Sleeper and Palmer 2005;Schmitz et al 2008) with occasional case descriptions of acquired cardiac disease (Reef 1987;Collatos et al 1990). However, the utility of echocardiography is not restricted to the diagnosis of anatomical abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Other congenital malformations of the great vessels, such as complete transposition (Sleeper and Palmer, 2005), persistent right aortic arch (Van der Linde-Sipman et al, 1979) and aortic origin of the right pulmonary artery (Reimer et al, 1993) have been reported occasionally.…”
mentioning
confidence: 99%